2014
DOI: 10.1007/s00382-014-2171-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Eurasian teleconnection pattern and its relationship to climate anomalies in China

Abstract: The Eurasian teleconnection pattern (EU) is a major mode of low-frequency variability in the Northern Hemisphere winter, with notable impacts on the temperature and precipitation anomalies in Eurasia region. To investigate the structure, life cycle and dynamical mechanisms of EU pattern, diagnostic analyses are conducted to clarify EU pattern evolution, with an emphasis on EU development and decay. In the developing stage, a geopotential height anomaly over North Atlantic emerges 6 days before EU peak phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Subsequent studies have indicated that this circumglobal pattern can significantly affect climate and weather over a broad area, including but not limited to East Asia and the latitudes of the Asian jet stream. For example, it may also induce precipitation anomalies over Europe, Japan, Northern China, and the Indian Monsoon regions [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have indicated that this circumglobal pattern can significantly affect climate and weather over a broad area, including but not limited to East Asia and the latitudes of the Asian jet stream. For example, it may also induce precipitation anomalies over Europe, Japan, Northern China, and the Indian Monsoon regions [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Teleconnection patterns are characterized by their planetary spatial scale and by the "seesaw" and/or wavelike structures in the horizontal direction at a monthly or seasonal mean timescale [6,7]. Previous studies have revealed that energy extraction from the background flow [7][8][9][10][11], quasi-stationary Rossby wave propagation [12][13][14], transient eddy feedback forcing [4,13,14], and the interaction between low-frequency circulation anomalies and background flow [15,16] are regarded as fundamental mechanisms for the formation and maintenance of teleconnection patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such teleconnection indices are El Niño-Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), North Atlantic Oscillation (NAO), West Pacific pattern (WP), Polar Eurasian pattern (POL), Pacific/North American (PNA) Pattern, and Scandinavia Pattern (SCA). These indices have been linked to interannual/interdecadal boreal precipitation variability [2,5,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%